2017
DOI: 10.1111/acem.13164
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Informed Consent for Computed Tomography in Acute Trauma Patients

Abstract: Background/Objective Computed tomography (CT) is common for trauma victims, but is usually done without informing patients of potential risks or obtaining informed consent. The objective of this study was to determine the feasibility of two elements (time and normal level of alertness) necessary for informed consent for CT in adult trauma patients. Methods We conducted this prospective observational, two-phase cohort study at two urban, Level 1 trauma centers. In the first phase, we determined the median tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Because of this exception, some physicians mistakenly believe that informed consent is not important when patients present to an emergency setting. However, most patients in emergency settings, including trauma patients, do not require immediate intervention to prevent death or serious harm and are competent to provide consent [2, 28]. For example, although this study does not address consent for surgical procedures, Moore et al reported that it is likely feasible to obtain informed consent for computed tomography in over two-thirds of adult acute trauma patients [28].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this exception, some physicians mistakenly believe that informed consent is not important when patients present to an emergency setting. However, most patients in emergency settings, including trauma patients, do not require immediate intervention to prevent death or serious harm and are competent to provide consent [2, 28]. For example, although this study does not address consent for surgical procedures, Moore et al reported that it is likely feasible to obtain informed consent for computed tomography in over two-thirds of adult acute trauma patients [28].…”
Section: Introductionmentioning
confidence: 99%